Hadith Isnad Study In The Discovery Of Islamic Law (Critique of the Thoughts of Goldziher and Schacht) - Tengku Azhar (Green Publisher Indonesia, 2024)
This study focuses on the examination of the isnad (chain of transmission) of hadith as a fundamental source and the second authority in determining Islamic law. Unlike the Qur'an, the authenticity of hadith, especially legal hadiths, remains a subject of extensive debate among hadith scholars, both Muslim thinkers and orientalists. Goldziher and Schacht are the primary pioneers in the critique of isnad studies. While Goldziher centered his research on hadith studies in general, Schacht focused specifically on the isnad of legal hadiths. This study's findings demonstrate that the 'conclusions' of Goldziher and Schacht are incorrect. Both scholars concluded that the isnad method only emerged in the second half of the second century Hijri. In reality, the isnad method existed much earlier than what Goldziher and Schacht had concluded. The second finding of this study indicates that the isnad of hadith significantly influences the determination of Islamic law among jurists (fuqaha’).